2020
DOI: 10.1111/bjd.19381
|View full text |Cite
|
Sign up to set email alerts
|

Biopsy outperforms reflectance confocal microscopy in diagnosing and subtyping basal cell carcinoma: results and experiences from a randomized controlled multicentre trial*

Abstract: Summary Background Reflectance confocal microscopy (RCM) is a noninvasive method for skin assessment, allowing entire lesion evaluation up to the papillary dermis. RCM is a potentially attractive alternative to punch biopsy (PB) in basal cell carcinoma (BCC). Objectives To determine the diagnostic accuracy of RCM vs. PB in diagnosing and subtyping BCC, and to study patient satisfaction and preferences. Methods Patients with a clinically suspected primary BCC were randomized between RCM and biopsy. Conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
0
21
0
1
Order By: Relevance
“…Lost in translation: true clinical impact of reflectance confocal microscopy overlooked in 'Biopsy outperforms reflectance confocal microscopy in diagnosing and subtyping basal cell carcinoma: results and experiences from a randomized controlled multicentre trial': reply from authors DEAR EDITOR, Firstly, we would like to thank M. Gill and colleagues for their interest shown in our study. 1,2 We agree on the importance of determining the place of reflectance confocal microscopy (RCM) as a diagnostic tool in real-world clinical practice, which is why we originally initiated our study. We chose to include patients with clinically suspected primary basal cell carcinoma (BCC), in which dermatoscopic evaluation was usually performed as well, as part of the daily clinical practice examination (as also mentioned by the authors as the current standard of many worldwide).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Lost in translation: true clinical impact of reflectance confocal microscopy overlooked in 'Biopsy outperforms reflectance confocal microscopy in diagnosing and subtyping basal cell carcinoma: results and experiences from a randomized controlled multicentre trial': reply from authors DEAR EDITOR, Firstly, we would like to thank M. Gill and colleagues for their interest shown in our study. 1,2 We agree on the importance of determining the place of reflectance confocal microscopy (RCM) as a diagnostic tool in real-world clinical practice, which is why we originally initiated our study. We chose to include patients with clinically suspected primary basal cell carcinoma (BCC), in which dermatoscopic evaluation was usually performed as well, as part of the daily clinical practice examination (as also mentioned by the authors as the current standard of many worldwide).…”
mentioning
confidence: 67%
“…Dear Editor , Firstly, we would like to thank M. Gill and colleagues for their interest shown in our study 1,2 . We agree on the importance of determining the place of reflectance confocal microscopy (RCM) as a diagnostic tool in real‐world clinical practice, which is why we originally initiated our study.…”
mentioning
confidence: 83%
“…ERP takes information technology as the carrier and stores the data through the database, and the user operates through the front-end interface, injecting the enterprise management idea into it. The core of the ERP system is the management culture of the enterprise, through the input of data, computing, and then output data to provide decision-making tools for employees at all levels of the enterprise and the decision-making level [13].…”
Section: Erp System Inventory Management Andmentioning
confidence: 99%
“…Dear Editor , In ‘Biopsy outperforms reflectance confocal microscopy in diagnosing and subtyping basal cell carcinoma: results and experiences from a randomized controlled multicentre trial’, the authors found that reflectance confocal microscopy (RCM) identifies basal cell carcinoma (BCC) with 99% sensitivity and, impressively, distinguishes superficial BCCs from more aggressive BCCs with 88·9% sensitivity compared with punch biopsy (PB) at 91%, 1 a difference without statistical significance. RCM’s imaging depth is limited to ~ 0·2 mm, but its advantage is comprehensive lateral sampling; PBs provide deep sampling, but demonstrate 18% discordance with wide excisions due to lateral sampling error 2 .…”
mentioning
confidence: 99%